2019
DOI: 10.3390/cancers12010011
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Surgical Wound Fluids from Breast Cancer Patients is Affected by Intraoperative Radiotherapy Treatment and Depends on the Molecular Subtype of Breast Cancer

Abstract: Invasive oncological procedures affect the remaining tumor cells by increasing their survival, proliferation, and migration through the induction of wound healing response. The phenomena of local relapse after breast-conserving surgery (BCS) has resulted in a series of research and clinical trials with the aim of assessing whether localized intraoperative radiotherapy (IORT), may be beneficial in inhibiting local recurrences. Therefore, it is essential to assess the impact of intraoperative radiotherapy in mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
6
21
0
3
Order By: Relevance
“…Confirming previous observations that IORT has an impact on cytokine levels within the WF [ 22 , 24 ], we observed that especially cytokines associated with wound healing and inflammation were modified by IORT. Oncostatin-M (OSM) was reduced in IORT-WF, whereas the levels of leptin and IL-1β were increased.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Confirming previous observations that IORT has an impact on cytokine levels within the WF [ 22 , 24 ], we observed that especially cytokines associated with wound healing and inflammation were modified by IORT. Oncostatin-M (OSM) was reduced in IORT-WF, whereas the levels of leptin and IL-1β were increased.…”
Section: Discussionsupporting
confidence: 91%
“…Belletti et al also observed significantly altered levels of the immune response-related cytokines IL-10 and IL-13 [ 22 ]. Elevated IL-1β levels were also reported by Kulcenty et al [ 24 ]. However, they observed that, only WF of Luminal A breast cancer patients, but not that of the Luminal B subtype [ 24 ] showed IORT-mediated increased IL-1β levels.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Those authors found that SWF from patients after BCS stimulates the proliferation, invasion, and migration of breast cancer cells, but administration of IORT abrogates this effect. Previously, we have conducted the quantitative analysis of SWF composition in breast cancer (BC) patients treated with BCS only, and BCS followed by IORT, and found significant changes based not only on the applied treatment but also on the molecular subtype of BC [11]. Moreover, our group showed that the radiation-induced bystander effect (RIBE) alters the biological activity of SWF after IORT [12,13].…”
Section: Introductionmentioning
confidence: 85%
“…It is known that irradiation changes the profile of secreted cytokines. We have previously shown that composition of SWF from BCS and IORT patients differs significantly based on cytokine and growth-factor concentrations [11].…”
Section: Discussionmentioning
confidence: 99%